EDUKASI-PENDAMPINGAN BUERGER ALLEN EXERCISE DAN 5 PILAR TERHADAP PERUBAHAN PENGETAHUAN DAN PERFORMA KESEHATAN FISIK PASIEN DIABETIK NEUROPATI PERIFER - Qomariah, Siti Nur; Susanti, Susanti; Kristiani, Rina Budi; Fajriyah, Novita; Suroso, Heri; Yobel, Sosilo; Bistara, Difran Nobel; Bakar, Abu (Community Development in Health Journal, 2023)
Introduction & Aim: Diabetes Mellitus patients with uncontrolled blood glucose levels for a long time will experience peripheral neuropathy complications with symptoms of tingling, numbness, pain in the feet, and disability in carrying out daily activities. The purpose of this community service was to evaluate Buerger Allen Exercise and 5 Pillars’ education on the knowledge and physical health performance of peripheral neuropathy diabetic patients. Method of Activity: Buerger Allen Exercise and 5 Pillars’ education was conducted on 28 diabetic patients with peripheral neuropathy who had previously been examined at the Gundih regional health center. This community service was carried out for 6 weeks at Jalan Kedinding RT 10 RW 01 Bubutan Surabaya with several stages of activity, namely: initial survey, education, application, assistance, and evaluation. Evaluated community behavior includes knowledge and physical health performance of diabetic peripheral neuropathy patients through measurement of the Ankle-Brachial Index (ABI), peripheral oxygen saturation in the feet (StO2), and physical activity ability. Data were analyzed using the Wilcoxon signed rank test and Paired t-test to evaluate the results of the service. Results: There were changes in community behavior such as knowledge increased by 21.5% (p=0.000); normal ABI by 57.1% (p=0.004); totally independent physical activity ability 92.9% (p=0.003), and normal StO2 100% (p=0.000). Discussion: Buerger Allen Exercise Education Assistance and 5 Pillars of Diabetes Mellitus provide optimal results in the management of diabetic peripheral neuropathy patients to prevent other complications such as diabetic ulcers, and amputation due to foot tissue death.